The future isn't working. Issue 3 (December 2015) - Srnicek, Nick; Williams, Alex
Abstract : Full employment is a tenet of classic social democracy – but what if that just isn't applicable anymore?Nick Srnicek andAlex Williams survey the state of the British labour market and ask how a modern Labour party might reframe the issue of work so that it is sustainable and sustaining in the face of technological change.